2021
DOI: 10.3390/app11093950
|View full text |Cite
|
Sign up to set email alerts
|

Material Removal Model for Lapping Process Based on Spiral Groove Density

Abstract: The increasing demand for single-crystal wafers combined with the increase in diameter of semiconductor wafers has warranted further improvements in thickness variation and material removal rate during lapping to ensure price competitiveness of wafers; consequently, the lapping process has gained the attention of researchers. However, there is insufficient research on the effect of platen grooves on the lapping process. In this study, the parameters to describe grooves were defined in order to understand their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Fig. 3 shows the polishing 6 µm diamond slurry is used on the Kemet copper lap with lapping load of 10N [6].…”
Section: Sapphire Lapping and Polishingmentioning
confidence: 99%
“…Fig. 3 shows the polishing 6 µm diamond slurry is used on the Kemet copper lap with lapping load of 10N [6].…”
Section: Sapphire Lapping and Polishingmentioning
confidence: 99%
“…Parks et al [9] reported lapping of sapphire wafers with #400 boron carbide (BC) abrasives on a cast-iron plate, observed a high material removal rate of 5-10 µm/min and achieved a surface roughness of 400-600 nm. Taekyung et al [10] used Kemet copper lap having grooves to hold the diamond slurry for longer durations, reported a low material removal rate of 0.5-1 µm/min, this improved the surface roughness of the wafer and obtained 10-20 nm Ra. Aida et al [11] reported chemical mechanical polishing of sapphire using poly urethane pad and colloidal silica as the slurry, achieved an excellent surface nish of 10-20 Å Ra and the material removal rate was very low 50 nm/hr.…”
Section: Introductionmentioning
confidence: 99%